Failure analysis of corroded pipelines reinforced with composite repair systems. (January 2016) - Costa Mattos, H.S. da; Reis, J.M.L.; Paim, L.M.; Silva, M.L. da; Lopes Junior, R.; Perrut, V.A.
Abstract: The present paper is concerned with the analysis of corroded thin-walled metallic pipes reinforced with polymer based composite repair systems. The goal is to propose a simple methodology to predict the failure pressure of a reinforced pipeline with arbitrary geometry of the corroded region and considering any composite repair system. Hydrostatic tests performed in different laboratories were used to validate the proposed methodology, showing that a simple expression allows estimating a lower bound for the failure pressure. Highlights: The focus is the rehabilitation of corroded pipelines with composite sleeves. A methodology to estimate the failure pressure of a reinforced pipe is presented. Model predictions are compared with the results of 54 different hydrostatic tests. There is a good agreement between model and experiments. The methodology is a valuable auxiliary tool for assessing the integrity of repaired pipelines.